2002
DOI: 10.1046/j.1471-4159.2002.01199.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the nematode putative GABA type‐A receptor subunits: evidence for modulation by ivermectin

Abstract: Two alleles of the HG1 gene, which encodes a putative GABA receptor a/c subunit, were isolated from Haemonchus contortus. These two alleles were shown previously to be associated with ivermectin susceptibility (HG1A) and resistance (HG1E), respectively. Sequence analysis indicates that they differ in four amino acids. To explore the functional properties of the two alleles, a full-length cDNA encoding the b subunit, a key functional component of the GABA receptor, was isolated from Caenorhabditis elegans (gab-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 22 publications
2
92
0
2
Order By: Relevance
“…It has been commonly observed that IVM does not affect mf motility or viability at pharmacologically relevant concentrations in culture (5,9), which is consistent with the apparent absence of GluCl expression in regions associated with somatic muscle function. Recently, it has been reported that IVM concentrations >1 μM affect mf motility (29); this may be associated with drug effects on GABA-gated chloride channels, which are secondary targets for the ML class (30). These effects may partially account for the concentration-dependence of the drug effect on secretion seen at the later time-point.…”
Section: Discussionmentioning
confidence: 99%
“…It has been commonly observed that IVM does not affect mf motility or viability at pharmacologically relevant concentrations in culture (5,9), which is consistent with the apparent absence of GluCl expression in regions associated with somatic muscle function. Recently, it has been reported that IVM concentrations >1 μM affect mf motility (29); this may be associated with drug effects on GABA-gated chloride channels, which are secondary targets for the ML class (30). These effects may partially account for the concentration-dependence of the drug effect on secretion seen at the later time-point.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to nematode acetylcholine receptors, these targets also include P2X receptors of Schistosoma [32] and of mouse ( [33]) and histamine-gated chloride channels of Drosophila [34], as well as nematode [35][36][37][38] and insect [39,40] glutamate-gated chloride channels, GABA receptors from nematodes to vertebrates [41][42][43][44] and human glycine receptors [45]. There is also evidence for an action of IVM on an intracellular ligand-gated ion channel, the ryanodine receptor [46].…”
Section: Ivermectin Can Have Allosteric and Agonist Effects On Ligandmentioning
confidence: 99%
“…In addition, long-term use and repeated dosing with these drugs may result in parasite resistance, as already observed in veterinary settings (Kaplan 2004) and some indication in the field (Awadzi et al 2004;Bourguinat et al 2007). Genetic basis for such phenomenon has been demonstrated (Feng et al 2002;Prichard 2007). There is thus a need for new effective and well-tolerated drugs.…”
Section: Introductionmentioning
confidence: 99%